The role of family and social media in athlete social interactions - Aulia Gusdernawati; Widiyanto (Journal Sport Area, 2021)
Social interaction is an inseparable part of human life, including an athlete, because literally, humans are social creatures. Social interactions carried out in society can be influenced by other factors such as family and social media. This study aims to determine how many roles out social media both on the social interaction of athletes. This research is quantitative research with the instrument used is a questionnaire. The population in this study was 70 National athletes from Riau Province. The analysis technique used is descriptive quantitative in the form of a percentage. The results revealed that the family has a good role with a value of 32.86%, while social media does not have enough roles with a percentage obtained of 40% and for both family and social media have a sufficient role of 34.29%. Social media and family have an adequate role for athletes in social interaction. This study has several limitations including the limited area and scope of research subjects.